Sexual Health Literacy, a Strategy for the Challenges of Sexual Life of Infertile Women: A Qualitative Study: - Rakhshaee, Zahra; Maasoumi, Raziyeh; Nedjat, Saharnaz; Khakbazan, Zohreh (Galen Medical Journal, 2020)
Background: Sexual health literacy enables an understanding and application of sexual health information and has benefits beyond health. Health literacy is an important element for achieving cognitive skills in health promotion. One of the most important problems in sexual health and sexual function in women is infertility. This study aims to explore the dimensions of sexual health literacy among women with infertility. Materials and Methods: In this qualitative study, a total of 18 individual interviews with 15 Iranian women with infertility, and three key informants, were conducted in infertility centers in Rasht (the North of Iran). Data were collected through in-depth semi-structured interviews using interview guide questions. Data were analyzed using the conventional content analysis approach. Results: Five themes emerged: informational needs of sexual health, information seeking, informational perception, validation of information, and information application. Sexual issues are taboo in Iranian culture. They are not taught in health and educational centers. All the participants believed that there was a lack of information about the sexual response cycle, preventing sexually transmitted infections, targeted intercourse, and consequences of infertility in sexual life. Participants mentioned the embarrassment, privacy, and lack of centers for sexual health as information-seeking barriers. Searching different sources and questioning the informants were ways for understanding information. Women evaluated the accuracy of the information by considering the validity of the source of information, comparing information from different sources, and asking the experts. They applied the information received about sexual health, satisfaction, and especially targeted intercourse to increase the chance of pregnancy. Conclusion: Sexual health literacy in infertile women includes different dimensions. It can help promote sexual health, satisfaction, and increasing the chance of pregnancy. [GMJ.2020;9:e1862]